Pregnancy with extrahepatic portal venous hypertension - Nabapure, Shilpa; S., Sapna I.; Sai, Balumuri Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
We are reporting a case of pregnancy with extrahepatic portal venous hypertension. Portal hypertension in pregnancy is an uncommon event. It presents a challenge to the obstetrician in management as physiological hemodynamic changes associated with pregnancy worsen with portal hypertension. Thus, increasing risk of life threatening complications like variceal haemorrhage and hepatic decompensation to many folds during pregnancy. Management requires knowledge of effects of portal hypertension on maternal and fetal outcome and vice-versa.